Vanadium-chlorine co-doped lithium iron phosphate material and preparation method thereof

The vanadium-chlorine co-doped lithium iron phosphate material addresses conductivity and ion mobility issues in LFP by combining carbon coating and nano-sizing, resulting in improved electrochemical performance and stability.

CN119118095APending Publication Date: 2024-12-13ANHUI UNIVERSITY OF ARCHITECTURE
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411102407.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-12
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The intrinsic conductivity and ion mobility of lithium iron phosphate (LFP) materials are low, limiting their performance in batteries, and existing modification methods like surface coating and particle size reduction have limitations.

Method used

A vanadium-chlorine co-doped lithium iron phosphate material (LVPC) is prepared through carbon coating and particle nano-sizing, combined with a simple carbothermal reduction method, to enhance conductivity and ion mobility.

Benefits of technology

The LVPC material exhibits improved electrochemical performance with enhanced structural stability, faster charging and discharging rates, and better cycle stability due to lattice distortion and reduced Li-O bond energy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118095A_ABST
    Figure CN119118095A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of electrochemical power supply materials, in particular to a vanadium-chlorine co-doped lithium iron phosphate material and a preparation method thereof. The preparation method comprises the following steps: step 1, mixing all materials into a parent raw material; 2, ball-milling and drying the raw materials to obtain a precursor; according to the vanadium and chlorine co-doped lithium iron phosphate material and the preparation method thereof, the method for preparing the vanadium and chlorine co-doped lithium iron phosphate material is simple, mature and low in cost, a V-Cl doped LiFePO4 sample is prepared by a simple carbon thermal reduction method, and the crystallinity is good; what's more important is that lattice of LiFePO4 is distorted, Li < + > mobility is increased due to reduction of Li-O bond energy in the lattice, meanwhile, structural stability of the material is improved due to increase of P-O bond energy, electrochemical test shows excellent cycling stability and rate capability, polarization effect is weakened, Li < + > diffusion coefficient is increased, and especially, vanadium and chlorine are doped, so that the performance of the material is greatly improved. And high-speed rapid charging and discharging are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrochemical power source material preparation, in particular to a vanadium-chlorine co-doped lithium iron phosphate material and a preparation method thereof. Background Art

[0002] Traditional fossil fuels are facing supply and demand contradictions and environmental problems, which have prompted people to realize the necessity of upgrading the energy consumption structure in order to cope with the challenges of climate change and environmental protection.

[0003] Lithium iron phosphate (LiFePO4, LFP) with high energy density, long cycle life and good stability has been widely used in electric vehicles, energy storage and other fields. The main problem restricting the further development of lithium iron phosphate batteries is that the intrinsic conductivity and ion mobility of lithium iron phosphate positive electrode materials are low. To this end, modification methods such as material surface coating, particle size reduction, and ion doping are used in strategies to improve the electrochemical performance of LFP. The most common method of surface coating is carbon coating, which constructs a fast conductive network through conductive carbon and lithium iron, thereby realizing the migration of electrons between active substances. In addition, it can inhibit the excessive growth of LFP particles and avoid Fe on the surface of the material. 2+ Oxidation increases the structural stability of the material. Particle nanosizing can significantly reduce the diffusion path of lithium ions inside the LFP material, achieve efficient intercalation and deintercalation, and improve the rate performance of the battery. At the same time, the increase in specific surface area increases the range of electrochemical reactions. Different from surface coating and reducing particle size, ion doping is an effective method to improve the intrinsic conductivity and ion conductivity of LFP positive electrode materials by distorting the lattice and reducing polarization and charge migration resistance. Ion doping can introduce the target element into the LFP lattice. On the one hand, it can inhibit the growth of particles, which is beneficial to particle nanosizing and improving the electrochemical properties of the material. On the other hand, the doped ions can induce lattice distortion through Li-site substitution or Fe-site substitution, weaken the Li-O bond effect, and improve Li + In addition, Fe 2+ / Fe 3+ The coexistence of mixed valence structures improves the conductivity of the material.

[0004] Ion doping can be divided into two types according to the doping elements: non-metallic element doping, such as nitrogen, boron, and chlorine; transition metal element doping, such as magnesium, manganese, cobalt, niobium, and vanadium. Studies have shown that compared with single-element doping, multi-element ion doping can couple the advantages of each element, promote the transmission performance of electrons, and improve the electrochemical performance of LFP. Among them, multivalent metal vanadium ions (V 5+ ) doping will cause lattice distortion and broaden the Li + transmission channel and inhibit the generation of Li / Fe antisite defects, thus improving Li + The diffusion rate and electronic conductivity of chloride ions (Cl- ) doping will occupy the three O-type sites individually or randomly, resulting in the extension of Li-O bond (the average Li-O bond length increases by 0.66%), the compression of PO bond (the average PO bond length decreases by 2.01%), and the reduction of Li + The resistance to migration can improve the structural stability of the material. Figure 1 As shown in Figure 2, first-principles calculations based on density functional theory show that V-Cl co-doping will cause LFP lattice volume expansion and distortion. Compared with pure LFP, the average Li-O bond length of V-Cl co-doped lithium iron phosphate (LVPC) is Grow to The average bond length of PO bonds is Shorten to The weakening of Li-O bond binding energy and the enhancement of PO bond binding energy reduce the Li + The resistance to migration is reduced, and the stability of the crystal structure is improved. The band gap between the valence band and the conduction band is reduced from 0.612eV to 0.285eV. The LVPC system is more prone to electronic transitions. In addition to Fe-3d, the V-3d orbital makes a greater contribution to the conduction band part close to the Fermi surface. In addition to the contributions of Fe-3d, V-3d and O-2p electron orbitals, the valence band part also includes some contributions from Cl-3p orbitals. The results show that the synergistic effect of anions and cations formed by the V-Cl co-doping system can effectively reduce the barrier of electronic energy band transition and improve electronic conductivity. Based on the general strategy of multi-element doping, the co-doping of V and Cl elements based on their respective doping characteristics is an effective way to further improve the comprehensive performance of LFP materials.

[0005] The present invention provides a method for preparing a vanadium-chlorine co-doped lithium iron phosphate material (abbreviated as LVPC / C) on the basis of carbon coating and particle nano-sizing. Summary of the invention

[0006] The object of the present invention is to provide a vanadium-chlorine co-doped lithium iron phosphate material and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0007] To achieve the above object, on the one hand, the present invention provides a method for preparing a vanadium-chlorine co-doped lithium iron phosphate material, comprising the following steps:

[0008] S1.1, mix all materials into parent raw materials;

[0009] S1.2, ball-milling and drying the raw materials to obtain a precursor;

[0010] S1.3. Calcine the precursor in a step-by-step manner to obtain the target product, vanadium-chlorine co-doped lithium iron phosphate material.

[0011] As a further improvement of this technical solution, the specific steps in S1.1 are as follows:

[0012] Add 3.69-3.71gLi2CO3, 17.70-18.12gFePO4·2H2O, 0.41-0.56gV2O5, 0.13-0.18gNH4Cl and 3.0-4.0g sucrose to 25-35ml ethanol, pour into a ball mill jar, add appropriate amount of ball milling beads and seal the jar, then put into a ball mill and mill at 300r / min for 8h to obtain a ball milled product.

[0013] As a further improvement of this technical solution, the specific steps in S1.2 are as follows:

[0014] The ball-milled product was transferred to a vacuum drying oven, heated to 60°C, kept warm for 12 h, and naturally cooled to room temperature to obtain a dry product, which was then poured into an agate mortar and ground to obtain a precursor.

[0015] As a further improvement of this technical solution, the specific steps in S1.3 are as follows:

[0016] The precursor is transferred to a calcination boat, placed in a tubular furnace, heated to 300-400°C in a nitrogen atmosphere, and kept warm for 3-5 hours for pre-calcination; the temperature is further raised to 650-750°C, kept warm for 8-12 hours for secondary calcination, and finally cooled to room temperature and ground to obtain vanadium-chlorine co-doped lithium iron phosphate material.

[0017] As a further improvement of the technical solution, the ball milling beads used in S1.1 are 3 mm zirconium oxide and weigh 70-80 g.

[0018] As a further improvement of the technical solution, the grinding time in S1.2 and S1.3 is 5-10 minutes.

[0019] On the other hand, the present invention provides a vanadium-chlorine co-doped lithium iron phosphate material prepared by any one of the preparation methods described above.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1. In the vanadium-chlorine co-doped lithium iron phosphate material and the preparation method thereof, the method for preparing the vanadium-chlorine co-doped lithium iron phosphate material is simple, mature, low-cost, and suitable for large-scale industrialization.

[0022] 2. In the vanadium-chlorine co-doped lithium iron phosphate material and its preparation method, a V-Cl-doped LiFePO4 sample was prepared by a simple carbothermal reduction method. The sample had a small grain size and good crystallinity. More importantly, the lattice of LiFePO4 was distorted, and the reduction of the Li-O bond energy in the lattice resulted in Li +The increase in mobility and the increase in PO bond energy improve the structural stability of the material.

[0023] 3. In the vanadium-chlorine co-doped lithium iron phosphate material and its preparation method, the advantages of the obtained doped lithium iron phosphate material are: electrochemical tests not only show excellent cycle stability and rate performance, but also show that the polarization effect is weakened, Li + The improved diffusion coefficient, especially vanadium-chlorine doping, enables fast charging and discharging at high rates. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The unit cell structure, electronic energy band and state density distribution diagram of LFP and LVPC calculated based on density functional theory;

[0025] Figure 2 The XRD patterns of LFP / C and LVPC / C obtained in Example 1 and Example 2 are shown in FIG.

[0026] Figure 3 The Fourier transform infrared spectra of LFP / C and LVPC / C obtained in Example 1 and Example 2 are shown;

[0027] Figure 4 The SEM photos and EDS mapping images of LFP / C and LVPC / C obtained in Example 1 and Example 2;

[0028] Figure 5 TEM and HRTEM images of LFP / C and LVPC / C obtained in Example 1 and Example 2;

[0029] Figure 6 The XPS spectra of LFP / C and LVPC / C obtained in Example 1 and Example 2;

[0030] Figure 7 The charge and discharge curves of the LFP / C and LVPC / C electrodes obtained in Example 1 and Example 2;

[0031] Figure 8 The electrochemical impedance diagrams of LFP / C and LVPC / C electrodes obtained in Example 1 and Example 2;

[0032] Fig. 9 Cyclic voltammograms of LFP / C and LVPC / C electrodes obtained in Example 1 and Example 2;

[0033] Fig.10 These are the rate long cycle diagrams of the LFP / C and LVPC / C electrodes obtained in Examples 1 and 2. DETAILED DESCRIPTION

[0034] The following will be combined with the accompanying drawings in the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0035] Example 1

[0036] In this embodiment, the carbon-coated and nano-particle vanadium-chlorine co-doped lithium iron phosphate battery is prepared according to the following steps:

[0037] Step 1: Add 3.69g Li2CO3, 17.74g FePO4·2H2O, 0.45g V2O5, 0.13g NH4Cl and 3.34g sucrose to 25ml ethanol, pour into a ball mill jar, add ball milling beads and seal the jar, then put into a ball mill, set the jar to run forward for 30min, stop for 5min, reverse for 30min, and mill at 300r / min for 8h to obtain a ball milled product;

[0038] Step 2: transfer the ball milled product to a vacuum drying oven, heat it to 60°C, keep it warm for 12 hours, cool it naturally to room temperature to obtain a dry product, and then pour the dry product into an agate mortar and grind it to obtain a precursor;

[0039] Step 3: Transfer the precursor to a calcination boat, place it in a tubular furnace, heat it to 300-400°C at 5°C / min in a nitrogen atmosphere, and keep it warm for 3-5 hours for pre-calcination; continue to heat it to 650-750°C at 5°C / min, keep it warm for 8-12 hours for secondary calcination, and finally cool it to room temperature and grind it to obtain vanadium-chlorine co-doped lithium iron phosphate material.

[0040] Step 4: Mix 120 mg of vanadium-chlorine co-doped lithium iron phosphate material, 15 mg of acetylene black and 15 mg of polyvinylidene fluoride (PVDF) in an agate mortar in a mass ratio of 8:1:1, add 1.5 mg of N-methyl-2-pyrrolidone (NMP) as a binder and mix thoroughly to form a uniform slurry, and evenly coat it on aluminum foil. Put the evenly coated aluminum foil into a vacuum drying oven and dry it at 60°C for more than 12 hours. Take out the dried aluminum foil and cut it into a cathode sheet with a diameter of 12 mm.

[0041] Step 5. Use high-purity lithium sheet and Celgard2400 as anode and diaphragm, take 50ml of 1mol / LLiPF6 ethylene carbonate / dimethyl carbonate (volume ratio of 1:1) solution as electrolyte, and assemble coin cells (named LVPC / C batteries) in a glove box with high-purity argon (oxygen and water values ​​are less than 0.1ppm) in the order of negative electrode shell-lithium sheet-electrolyte-diaphragm-electrolyte-electrode sheet-gasket-spring-positive electrode shell from bottom to top.

[0042] Example 2

[0043] In this embodiment, the carbon-coated and nano-particle vanadium-chlorine co-doped lithium iron phosphate battery is prepared according to the following steps:

[0044] Step 1: Add 3.69g Li2CO3, 18.68g FePO4·2H2O, and 3.35g sucrose to 25ml ethanol, pour into a ball mill jar, add ball milling beads and seal the cover, then put it into a ball mill, set it to run forward for 30min, stop for 5min, reverse for 30min, and ball mill at 300r / min for 8h to obtain a ball milled product.

[0045] Step 2: Transfer the ball-milled product to a vacuum drying oven, heat it to 60°C, keep it warm for 12 hours, and naturally cool it to room temperature to obtain a dry product. Then pour the dry product into an agate mortar and grind it to obtain a precursor.

[0046] Step 3: Transfer the precursor to a calcination boat, place it in a tubular furnace, heat it to 300-400°C at 5°C / min in a nitrogen atmosphere, and keep it warm for 3-5 hours for pre-calcination; continue to heat it to 650-750°C at 5°C / min, keep it warm for 8-12 hours for secondary calcination, and finally cool it to room temperature and grind it to obtain lithium iron phosphate material.

[0047] Step 4: Mix 120 mg of vanadium-chlorine co-doped lithium iron phosphate material, 15 mg of acetylene black and 15 mg of polyvinylidene fluoride (PVDF) in an agate mortar in a mass ratio of 8:1:1, add 1.5 mg of N-methyl-2-pyrrolidone (NMP) as a binder and mix thoroughly to form a uniform slurry, and evenly coat it on aluminum foil. Put the evenly coated aluminum foil into a vacuum drying oven and dry it at 60°C for more than 12 hours. Take out the dried aluminum foil and cut it into cathode sheets with a diameter of 12 mm.

[0048] Step 5. Use high-purity lithium sheet and Celgard2400 as anode and diaphragm, take 50ml of 1mol / LLiPF6 ethylene carbonate / dimethyl carbonate (volume ratio of 1:1) solution as electrolyte, and assemble coin cells (named LFP / C batteries) in a glove box with high-purity argon (oxygen and water values ​​are less than 0.1ppm) in the order of negative electrode shell-lithium sheet-electrolyte-diaphragm-electrolyte-electrode sheet-gasket-spring-positive electrode shell from bottom to top.

[0049] Figure 2 The XRD patterns of LFP / C and LVPC / C obtained in Example 1 and Example 2 clearly show that the diffraction peaks of the samples correspond to the standard olivine-type LiFePO4 (JCPDS81-1173), with a small half-width and sharper diffraction peaks, indicating that all samples are well crystallized and belong to the ordered olivine structure of orthorhombic Pnma. During the preparation process, sucrose is simultaneously decomposed into amorphous carbon at high temperature and coated on the surface of LFP crystals, which improves the conductivity of LFP without changing the crystal morphology. In addition, no diffraction peaks of other impurities are observed, indicating that the synthesized samples are very pure.

[0050] Figure 3 The Fourier transform infrared spectra of LFP / C and LVPC / C obtained in Example 1 and Example 2 are used to characterize the difference in conductivity between the samples. Figure 3 The frequency range can be divided into four parts for analysis: First, a frequency of 971cm -1 The single absorption peak at 469 cm -1 and 502cm -1 The double peak at 1052-1138 cm is related to the symmetric bending vibration of the OPO bond; then -1 The region between 550 and 635 cm is consistent with the antisymmetric stretching vibration of the P-O bond; finally, -1 The absorption peak at 1052 cm is caused by the antisymmetric bending of the OPO bond. -1 、971cm -1 and 502cm -1 The frequency of PO4 has different degrees of red shift, which is because the electronegativity of Cl is stronger than that of O, and Cl induces 3- Therefore, doping with Cl helps to improve the intrinsic conductivity of LFP / C composites and enhance the electrochemical properties of the materials.

[0051] Figure 4The SEM photos and EDS mapping of LFP / C and LVPC / C obtained in Example 1 clearly show that the sample particles are uniform and the diameter is evenly distributed between 200-300nm. The results show that V-Cl doping has little effect on the overall morphology of LiFePO4 material. However, compared with LFP / C ( Figure 4 a) Compared with LVPC / C, the particle size is smaller ( Figure 4 b), more dispersed and less agglomerated. Small particles can not only increase the contact area between the material and the electrolyte, but also shorten the Li + Diffusion path of Li + The shorter the migration path, the better the Li + The migration rate of LFP / C is improved, thereby improving the electrochemical performance of LFP / C. In order to study the distribution of constituent elements in the particles, we conducted EDS tests, such as Figure 4 As shown in Figure 3, the uniform distribution of V and Cl can be easily observed, confirming that the V and Cl elements are well integrated with LiFePO4.

[0052] Figure 5 TEM and HRTEM images of LFP / C and LVPC / C obtained in Example 1 and Example 2. The particle size of LVPC / C is 300 nm, which is consistent with the SEM result. In addition, it can be observed in the HRTEM image that the outer layer of the LVPC particles is wrapped by an amorphous carbon layer with a thickness of about 3 nm ( Figure 5 a). Figure 5 (b) The measurement of lattice fringes shows that the lattice fringes spacing of LVPC / C is 0.252nm, corresponding to the (311) crystal plane. This high crystallinity and good carbon coating treatment also provide a good basis for improving the electrochemical performance of cathode materials.

[0053] Figure 6 XPS spectra of LFP / C and LVPC / C obtained in Example 1 and Example 2, where: (a) corresponds to the full spectrum; (b) corresponds to the Fe-2p peak of LFP / C and LVPC / C; (c) corresponds to the V-2p peak of LVPC / C; (d) corresponds to the Cl-2p peak of LVPC / C. Figure 6 (a) XPS overall spectrum, we can clearly see the peaks corresponding to Li-1s, P-2s, P-2p, Cl-2p, C-1s, V-2p, O-1s and Fe-2p. Figure 6 (b) shows the high-resolution XPS spectra of Fe-2p in all samples. Due to spin-orbit coupling, the spectrum of Fe-2p is divided into two peaks, namely, Fe-2p 3 / 2 and Fe-2p 1 / 2The binding energies of the characteristic peaks are 709.38 and 723.18 eV respectively. The binding energy is 13.8 eV. In addition, the binding energy values ​​of 712.18 eV and 726.48 eV are two typical satellite peaks of Fe-2p. Figure 6 (c) 516.08eV, 523.28eV and V-2p 3 / 2 、V-2p 1 / 2 In addition, note that the Cl-2p peak at 198.2 eV overlaps with the P-2s peak at 191.6 eV. Since the content of P is much higher than that of Cl, the Cl-2p peak is very weak and cannot be observed clearly. However, it can be seen from Figure 6 The Cl-2p peak is identified in the enlarged panel of (d), and the satellite peaks at 197.28 eV and 199.18 eV further confirm the presence of Cl in the sample.

[0054] Figure 7 The LFP / C and LVPC / C electrodes obtained in Example 1 and Example 2 were tested under the constant current mode of 2.5V-4.2V (1C = 170mAh·g -1 ) charge and discharge curves. The material LVPC / C exhibits excellent electrochemical performance with a capacity of 144.12mAh / g and 130.27mAh / g under 1C and 5C discharge conditions, respectively. In contrast, the capacity of LFP / C is only 130.99mAh / g and 109.57mAh / g at the corresponding discharge rates. Figure 7 It can be clearly observed in (a) and (b) that around 3.4V, LVPC / C has a flat and stable voltage platform, indicating that during this period, the main reaction is the transfer reaction between the two phases of LiFePO4 and FePO4. With the increase of the working current density, due to the slow diffusion kinetics of Li ions, the battery polarization becomes more and more serious, and the battery capacity gradually decreases. At different rates, the charge and discharge voltage platform of LVPC / C is more stable than that of LFP / C, the gap between the platforms is smaller, and it has a higher discharge capacity, indicating that LVPC / C has smaller electrochemical polarization and has better electrochemical performance than LFP / C. It is worth noting that at high discharge rates, the difference in discharge specific capacity between doped and undoped materials is particularly obvious, such as Figure 7(c) shows the cycling reversibility of LFP / C and LVPC / C electrodes at different rates. The discharge specific capacity of LVPC / C at high rates of 5C and 10C is 130.03mAh / g and 120.04mAh / g, which is much higher than the 109.24mAh / g and 100.62mAh / g of the undoped samples. Obviously, at high rates, LVPC / C has a higher specific capacity than LFP / C. This is because after V-Cl doping, LiFePO4 undergoes lattice distortion, the ion vacancy concentration increases, shortens the band gap width of LFP, and expands the lattice spacing and the diffusion path of Li ions. At the same time, the generated crystals have a larger cell volume and reduce polarization during charge and discharge, thereby improving the electrochemical performance of LiFePO4. Finally, when the current density is reset to 1C after the battery is charged and discharged at a high rate of 10C, the specific capacity of all samples does not decrease, which proves that the synthesized material has good stability and reversibility, and the structure of the material will not be destroyed during high-rate charge and discharge.

[0055] Figure 8 AC impedance tests were performed for the LFP / C and LVPC / C electrodes of Examples 1 and 2. The test frequency was set to 0.01-100000 Hz and the amplitude was 5 mV. Figure 8 (a) is the electrochemical impedance spectra (EIS) of all materials. The results further show that co-doping with appropriate elements can effectively improve the diffusion kinetics of LFP / C electrode materials and reduce impedance. The reduction of charge transfer impedance during charge and discharge is conducive to overcoming the dynamic limitations of the process, thereby increasing the insertion / extraction depth of lithium ions during high-rate charge and discharge and improving electrochemical performance. Figure 8 (b) is the square root of the impedance-angular frequency relationship (Z' vs ω) calculated from the EIS spectrum. -1 / 2 As shown in Table 1, compared with the undoped LFP / C electrode material, the charge transfer impedance R ct (291.5Ω) is much smaller than the R of LFP / C ct (215.2Ω). LVPC / C has a higher exchange current density (i0=11.94×10 - 5 mA·cm -2 ) and the lithium ion diffusion coefficient (D Li =3.03×10 -16 cm 2 ·s -1 ), indicating that it has the best electrochemical reactivity and reversibility. The exchange current density and lithium ion diffusion coefficient after V-Cl doping are higher, which may be due to grain refinement and weakening of Li-O bonds in the crystal structure. The diffusion channel of lithium ions along the (010) direction is broadened and the diffusion rate of lithium ions is accelerated, which is consistent with its good electrochemical performance.

[0056] Fig. 9 The cyclic voltammograms of the LFP / C and LVPC / C electrodes obtained in Example 1 and Example 2 at a scan rate of 0.5 mV / s are shown in FIG. Fig. 9 As shown in (a), the oxidation peak and reduction peak of LFP / C are 3.68V and 3.23V, respectively, with a peak potential difference of 0.45V. In contrast, the oxidation peak and reduction peak of LVPC / C are 3.66V and 3.27V, respectively, with a peak potential difference of 0.39V, which is considered to have smaller polarization and better kinetics. Doping shifts the oxidation peak to the left and the reduction peak to the right, which reduces the potential difference of the redox peaks and weakens the polarization. LVPC / C has the characteristics of minimal redox potential difference, symmetrical peak height, large peak current, and excellent electrochemical reaction kinetics. In order to further investigate the joint effects of V and Cl on the kinetic process after incorporation into the LFP lattice, we conducted electrochemical experiments on all materials at 2.5V and 4.2V (vs. Li / Li + ) were analyzed at different scan rates in the cut-off potential window. The results are shown in Fig. 9 (b) and (c). At different scanning speeds, the reduction and oxidation peaks of all samples show highly symmetrical peaks, indicating that the deintercalation / intercalation of Li ions in LFP crystals has good cyclic reversibility. As the scanning rate increases, the shape of the CV curve does not change much, but the oxidation peak moves to a higher potential, while the corresponding reduction peak moves to a lower potential. The difference between the oxidation peak and the reduction peak gradually increases, indicating that the polarization effect gradually increases.

[0057] Fig.10 Long rate cycle diagrams of LFP / C and LVPC / C obtained in Examples 1 and 2. Fig.10 (a) After 1000 cycles at 1C, the capacity retention rate of LFP / C is about 72%, and the capacity of LVPC / C battery is still 128.06 mAh g after 1000 cycles. -1 , the capacity retention rate is 89%. Fig.10 (b) After 1000 cycles at 5C, the capacity retention rate of LFP / C is about 61%, and the capacity of LVPC / C battery is still 108.02 mAh g after 1000 cycles. -1 , the capacity retention rate is 83%. The results show that V-Cl co-doping can effectively improve the cycle stability of LFP.

[0058] Table 1 is a table of electrochemical impedance parameters of the LFP / C and LVPC / C electrodes obtained in Example 1 and Example 2.

[0059] sample <![CDATA[R ct (Oh)]]> <![CDATA[i0(mA·cm -2 )]]> <![CDATA[D Li (cm 2 ·s -1 )]]> LFP / C 291.5 <![CDATA[8.81×10 -5 ]]> <![CDATA[1.88×10 -16 ]]> LVPC / C 215.2 <![CDATA[11.94×10 -5 ]]> <![CDATA[3.03×10 -15 ]]>

[0060] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments. The above embodiments and descriptions are only preferred examples of the present invention and are not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing vanadium-chlorine co-doped lithium iron phosphate material, It is characterized in that The following steps are involved: S1.1, mix all materials into parent raw materials; S1.2, ball-milling and drying the raw materials to obtain a precursor; S1.

3. Calcine the precursor in a step-by-step manner to obtain the target product, vanadium-chlorine co-doped lithium iron phosphate material.

2. The method for preparing the vanadium-chlorine co-doped lithium iron phosphate material according to claim 1, It is characterized in that The specific steps in S1.1 are as follows: 3.69-3.71gLi 2 CO 3 、17.70-18.12gFePO 4 ·2H 2 O, 0.41-0.56gV 2 O 5 , 0.13-0.18gNH 4 Cl and 3.0-4.0 g sucrose were added to 25-35 ml ethanol, poured into a ball mill jar, added with an appropriate amount of ball milling beads and sealed, and then put into a ball mill and ball milled at 300 r / min for 8 h to obtain a ball milled product.

3. The method for preparing the vanadium-chlorine co-doped lithium iron phosphate material according to claim 2, It is characterized in that The specific steps in S1.2 are as follows: The ball-milled product was transferred to a vacuum drying oven, heated to 60°C, kept warm for 12 h, and naturally cooled to room temperature to obtain a dry product, which was then poured into an agate mortar and ground to obtain a precursor.

4. The method for preparing the vanadium-chlorine co-doped lithium iron phosphate material according to claim 3, It is characterized in that The specific steps in S1.3 are as follows: Transfer the precursor to a calcination boat, place it in a tube furnace, heat it to 300-400°C in a nitrogen atmosphere, and keep it at this temperature for 3-5 hours for pre-calcination; The temperature is continued to be raised to 650-750° C., kept at this temperature for 8-12 hours for two-stage calcination, and finally cooled to room temperature and ground to obtain vanadium-chlorine co-doped lithium iron phosphate material.

5. The method for preparing the vanadium-chlorine co-doped lithium iron phosphate material according to claim 2, It is characterized in that The ball milling beads used in S1.1 are 3 mm zirconium oxide and weigh 70-80 g.

6. The method for preparing vanadium-chlorine co-doped lithium iron phosphate material according to claim 4, It is characterized in that The grinding time in S1.2 and S1.3 is 5-10 min.

7. A vanadium-chlorine co-doped lithium iron phosphate material prepared by the preparation method according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Method for preparing chlorine ion doped iron lithium phosphate powder body

    CN101293641A

  • Synthesis method for lithium iron phosphate / carbon composite material

    CN102332565A

  • Fluorine and vanadium ion-doped lithium iron phosphate material and preparation method thereof

    CN102583300A

  • IN261KO2011A